A ZnO / ZnS composite material with zinc and oxygen double vacancies and its preparation method and application

By preparing ZnO/ZnS composite materials with double vacancies of zinc and oxygen, the problem of low hydrogen production efficiency in the prior art is solved, and more efficient photocatalytic activity and hydrogen production efficiency are achieved.

CN118002152BActive Publication Date: 2025-03-11QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410255290.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2025-03-11
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

When existing ZnO/ZnS composite materials produce hydrogen by photocatalytic cracking, the photogenerated carrier utilization rate is low, resulting in low efficiency.

Method used

A ZnO/ZnS composite material with zinc and oxygen double vacancies is used. This material is prepared by solvothermal method and hydrothermal treatment to form a hollow spherical structure and an internal electric field structure, which increases the surfactant site and visible light absorption range.

Benefits of technology

The efficiency of hydrogen production by photocatalytic decomposition of water is significantly improved, and the efficiency of hydrogen production is 12 times higher than that of ordinary ZnO/ZnS composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118002152B_ABST
    Figure CN118002152B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of preparation and application of inorganic functional composite materials, and relates to a ZnO / ZnS composite material with zinc and oxygen double vacancies, and a preparation method and application thereof. The ZnO / ZnS composite material with zinc and oxygen double vacancies provided by the present invention has a hollow spherical structure, which has a higher specific surface area and can provide more surface active sites; at the same time, the zinc and oxygen double vacancy structure can shorten the band gap of the semiconductor, thereby improving the utilization rate of visible light. At the same time, the presence of vacancies can adjust the internal electronic structure of the material to improve the photocatalytic activity. Compared with single ZnO, the ZnO / ZnS composite material with zinc and oxygen double vacancies provided by the present invention shows excellent photocatalytic water decomposition hydrogen production performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation and application of inorganic functional composite materials, and relates to a ZnO / ZnS composite material with zinc and oxygen double vacancies and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The photocatalytic activity of single ZnO can be improved by constructing ZnO / ZnS composite materials using existing technologies.

[0004] However, photocatalysts with only heterojunctions lack effective adsorption sites for reactants on their surfaces, resulting in low utilization of photogenerated carriers, which in turn affects the efficiency of photocatalytic water splitting to produce hydrogen. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a ZnO / ZnS composite material with zinc and oxygen double vacancies and its preparation method and application. The ZnO / ZnS composite material provided by the present invention not only has a higher specific surface area, can provide more surface active sites, and promote photocatalytic decomposition of water to produce hydrogen; but also has a zinc and oxygen double vacancy structure, which can shorten the band gap of the semiconductor, thereby improving the utilization rate of visible light. At the same time, the presence of vacancies can adjust the internal electronic structure of the material to improve the photocatalytic activity.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, a ZnO / ZnS composite material having zinc and oxygen double vacancies is provided, wherein the ZnO / ZnS composite material is a hollow spherical structure, and there are zinc vacancy and oxygen vacancy signals in the electron paramagnetic self-resonance (EPR) spectrum of the ZnO / ZnS composite material.

[0008] The ZnO / ZnS composite material with zinc and oxygen double vacancies provided by the present invention has the advantages of 3D structure, large specific surface area and excellent visible light activity, etc. At the same time, ZnO and ZnS form a heterojunction structure with an internal electric field that significantly promotes the separation and migration of photogenerated carriers, and the double vacancy structure therein can adjust the electronic structure inside the material, greatly expanding the visible light absorption range of the material. The synergistic effect of the above characteristics enables the composite material to exhibit excellent photocatalytic activity.

[0009] The present invention unexpectedly discovered through experiments that, compared with the common ZnO / ZnS composite material, the ZnO / ZnS composite material with zinc and oxygen double vacancies provided by the present invention has more significant photocatalytic hydrogen production activity, which can be obtained from 10.95mmol·g -1 ·h -1 The level (common ZnO / ZnS composite material) was increased to 132.51mmol·g -1 ·h -1 Level (the present invention).

[0010] In a second aspect, a method for preparing the above-mentioned ZnO@ZnS composite material having zinc and oxygen double vacancies comprises the following steps:

[0011] A zinc salt, a template agent, and a chelating agent are mixed to prepare a precursor by a solvothermal method, and then the precursor is calcined in an air atmosphere to obtain a ZnO hollow sphere material;

[0012] The ZnO hollow sphere material and thiourea are dispersed in water and mixed evenly, and then subjected to hydrothermal treatment, and then calcined in an inert atmosphere to obtain the hollow sphere.

[0013] The present invention has found through experiments that the obtained ZnO / ZnS composite material can not only have oxygen vacancies, but also generate zinc vacancies, thereby obtaining a ZnO@ZnS composite material with zinc and oxygen double vacancies.

[0014] In a third aspect, an application of the above-mentioned ZnO@ZnS composite material having zinc and oxygen double vacancies in photocatalytic water decomposition to produce hydrogen.

[0015] The beneficial effects of the present invention are:

[0016] The ZnO / ZnS composite material with zinc and oxygen double vacancies prepared by the present invention first adopts a hydrothermal ion exchange method to obtain the ZnO / ZnS composite material. Compared with the preparation method of other composite materials, it is simpler, more efficient and energy-saving. In addition, because the composite material is prepared by ion exchange, its structure is stable and it is not easy to fall off between components. At the same time, the close combination between interfaces can shorten the transmission distance of photogenerated carriers. The material obtained by ion exchange is calcined under a reducing atmosphere of argon to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies. The ZnO in the ZnO / ZnS composite material with zinc and oxygen double vacancies in the present invention has a hollow spherical structure with a significantly increased specific surface area, which can provide more reactive sites and is conducive to the adsorption of reactants. At the same time, the ZnO / ZnS material obtained after ion exchange forms an internal electric field structure that significantly promotes the separation and migration of photogenerated carriers and improves its photocatalytic performance. Moreover, the ZnO / ZnS composite material with zinc and oxygen double vacancies can adjust the electronic structure inside the material, thus expanding the visible light absorption range of the material. The synergistic effect of the above characteristics makes the composite material exhibit excellent photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 It is the X-ray diffraction pattern (XRD) of ZnO prepared in Examples 1, 3, 5 and 7 of the present invention and the ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0019] Figure 2 This is a transmission electron microscope (TEM) of the ZnO hollow sphere material prepared in Example 1 of the present invention.

[0020] Figure 3 This is a transmission electron microscope (TEM) of the ZnO / ZnS composite material with zinc and oxygen double vacancies prepared in Example 5 of the present invention.

[0021] Figure 4 This is an element energy distribution surface scanning spectrum (EDS mapping) of the ZnO / ZnS composite material with zinc and oxygen double vacancies prepared in Example 5 of the present invention.

[0022] Figure 5 The hollow ZnO sphere material prepared in Examples 1 and 5 of the present invention and the ZnO / ZnS composite material with zinc and oxygen double vacancies are used for electron paramagnetic self-resonance (EPR).

[0023] Figure 6It is a performance diagram of photocatalytic water decomposition and hydrogen production of ZnO hollow sphere materials prepared in Examples 1-7 of the present invention, ordinary ZnO / ZnS composite materials and ZnO / ZnS composite materials with zinc and oxygen double vacancies. DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0026] In view of the problem that the existing ZnO / ZnS composite materials have low efficiency in photocatalytic water splitting to produce hydrogen, the present invention proposes a ZnO / ZnS composite material with zinc and oxygen double vacancies and a preparation method and application thereof.

[0027] A typical embodiment of the present invention provides a ZnO / ZnS composite material having zinc and oxygen double vacancies, wherein the ZnO / ZnS composite material has a hollow spherical structure, and there are signals of zinc vacancies and oxygen vacancies in the electron paramagnetic self-resonance (EPR) spectrum of the ZnO / ZnS composite material.

[0028] In some embodiments, the EPR spectrum is as follows Figure 5 shown.

[0029] Another embodiment of the present invention provides a method for preparing the above-mentioned ZnO@ZnS composite material having zinc and oxygen double vacancies, comprising the following steps:

[0030] A zinc salt (such as zinc acetate), a template (such as PVP), and a chelating agent (such as salicylic acid) are mixed to prepare a precursor by a solvothermal method, and then the precursor is calcined in an air atmosphere to obtain a ZnO hollow sphere material;

[0031] The ZnO hollow sphere material and thiourea are dispersed in water and mixed evenly, and then subjected to hydrothermal treatment, and then calcined in an inert atmosphere to obtain the hollow sphere.

[0032] In some embodiments, the mass ratio of zinc salt, template agent, and chelating agent is 0.3-0.5:1:0.25-0.35.

[0033] In some embodiments, the solvent for the solvothermal reaction is ethanol.

[0034] In some embodiments, the temperature of the solvothermal reaction is 150-170° C., and the time is 9-11 h.

[0035] In some embodiments, the calcination temperature in air atmosphere is 450-550°C, the calcination time is 2.5-3.5h, and the heating rate in air atmosphere is 0.5-1.5°C·min -1 .

[0036] In some embodiments, the temperature of the hydrothermal treatment is 155-165° C., and the time is 22-26 hours.

[0037] In some embodiments, the molar ratio of the ZnO hollow sphere material to thiourea is 0.2 to 1:1, and may be 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1, etc.

[0038] In some embodiments, the calcination temperature in an inert atmosphere is 300-400°C, the calcination time is 2.5-3.5 hours, and the heating rate in an inert atmosphere is 1-3°C·min -1 .

[0039] A third embodiment of the present invention provides an application of the above-mentioned ZnO@ZnS composite material having zinc and oxygen double vacancies in photocatalytic water decomposition to produce hydrogen.

[0040] Specifically, the ZnO@ZnS composite material having zinc and oxygen double vacancies is added to a solution containing sodium sulfide and sodium sulfite, mixed evenly, and irradiated with light.

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0042] Embodiment 1:

[0043] A method for preparing ZnO hollow spheres comprises the following steps: dissolving 1g of PVP in 50mL of ethanol solution, stirring at 350rpm for 30min at room temperature to dissolve it, then adding 0.4g of zinc acetate dihydrate and 0.3g of salicylic acid, and magnetically stirring at room temperature for 4h. The clear solution is transferred to a 100ml polytetrafluoroethylene-lined reactor, and subjected to solvent thermal treatment in an oven at 160°C for 10h. After cooling naturally to room temperature, the obtained precipitate is centrifuged, washed, dried, and ground, and the ground white powder is annealed in a tube furnace at 1°C·min -1 The temperature was raised to 500°C and calcined for 3 hours, then naturally cooled and ground to obtain ZnO hollow spheres.

[0044] Embodiment 2:

[0045] A preparation method of a common ZnO / ZnS composite material (denoted as ZnO / ZnS) comprises the following steps: dissolving 1g PVP in 50mL ethanol solution, stirring at 350rpm for 30min at room temperature to dissolve it, then adding 0.4g zinc acetate dihydrate and 0.3g salicylic acid, and magnetically stirring at room temperature for 4h. The clear solution is transferred to a 100ml polytetrafluoroethylene-lined reactor and subjected to solvent thermal treatment in an oven at 160°C for 10h. After cooling naturally to room temperature, the obtained precipitate is centrifuged, washed, dried, and ground, and 0.1g of white powder and 0.054g of thiourea after grinding are added to 30mL deionized water to form a uniform suspension. After ultrasonic treatment for 15min, the suspension is continuously stirred at room temperature for 30min, and the obtained suspension is transferred to a 100ml polytetrafluoroethylene-lined reactor and subjected to hydrothermal treatment in an oven at 160°C for 24h. After cooling naturally to room temperature, the obtained precipitate is centrifuged, washed, dried and ground to obtain a common ZnO / ZnS composite material.

[0046] Embodiment 3:

[0047] A method for preparing a ZnO / ZnS composite material with zinc and oxygen double vacancies (denoted as ZOS-1) comprises the following steps:

[0048] Add 0.1 g of ZnO hollow spheres prepared in Example 1 and 0.018 g of thiourea to 30 mL of deionized water to form a uniform suspension. After ultrasonic treatment for 15 min, stir continuously at room temperature for 30 min, transfer the resulting suspension to a 100 ml polytetrafluoroethylene-lined reactor, and hydrothermally treat it in an oven at 160 ° C for 24 h. After cooling naturally to room temperature, the resulting precipitate is centrifuged, washed, dried, and ground to obtain a white powder. Weigh 0.1 g of the white powder and place it in a porcelain boat, which is placed in a tubular furnace under an argon atmosphere at 2 ° C·min -1 The temperature was raised to 350°C and calcined for 2 hours, and then naturally cooled and ground to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0049] Embodiment 4:

[0050] A method for preparing a ZnO / ZnS composite material with zinc and oxygen double vacancies (denoted as ZOS-2) comprises the following steps:

[0051] Add 0.1 g of ZnO hollow spheres prepared in Example 1 and 0.036 g of thiourea to 30 mL of deionized water to form a uniform suspension. After ultrasonic treatment for 15 min, stir continuously at room temperature for 30 min, transfer the resulting suspension to a 100 ml polytetrafluoroethylene-lined reactor, and hydrothermally treat it in an oven at 160 ° C for 24 h. After cooling naturally to room temperature, the resulting precipitate is centrifuged, washed, dried, and ground to obtain a white powder. Weigh 0.1 g of the white powder and place it in a porcelain boat, which is placed in a tubular furnace under an argon atmosphere at 2 ° C min -1 The temperature was raised to 350°C and calcined for 2 hours, and then naturally cooled and ground to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0052] Embodiment 5:

[0053] A method for preparing a ZnO / ZnS composite material with zinc and oxygen double vacancies (denoted as ZOS-3) comprises the following steps:

[0054] Add 0.1 g of ZnO hollow spheres prepared in Example 1 and 0.054 g of thiourea to 30 mL of deionized water to form a uniform suspension. After ultrasonic treatment for 15 min, stir continuously at room temperature for 30 min, transfer the resulting suspension to a 100 ml polytetrafluoroethylene-lined reactor, and hydrothermally treat it in an oven at 160 ° C for 24 h. After cooling naturally to room temperature, the resulting precipitate is centrifuged, washed, dried, and ground to obtain a white powder. Weigh 0.1 g of the white powder and place it in a porcelain boat, which is placed in a tubular furnace under an argon atmosphere at 2 ° C·min -1 The temperature was raised to 350°C and calcined for 2 hours, and then naturally cooled and ground to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0055] Embodiment 6:

[0056] A method for preparing a ZnO / ZnS composite material (denoted as ZOS-4) with zinc and oxygen double vacancies comprises the following steps:

[0057] Add 0.1 g of ZnO hollow spheres prepared in Example 1 and 0.072 g of thiourea to 30 mL of deionized water to form a uniform suspension. After ultrasonic treatment for 15 min, stir continuously at room temperature for 30 min, transfer the resulting suspension to a 100 ml polytetrafluoroethylene-lined reactor, and hydrothermally treat it in an oven at 160 ° C for 24 h. After cooling naturally to room temperature, the resulting precipitate is centrifuged, washed, dried, and ground to obtain a white powder. Weigh 0.1 g of the white powder and place it in a porcelain boat, which is placed in a tubular furnace under an argon atmosphere at 2 ° C·min -1 The temperature was raised to 350°C and calcined for 2 hours, and then naturally cooled and ground to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0058] Embodiment 7:

[0059] A method for preparing a ZnO / ZnS composite material (denoted as ZOS-5) having zinc and oxygen double vacancies comprises the following steps:

[0060] Add 0.1 g of ZnO hollow spheres prepared in Example 1 and 0.09 g of thiourea to 30 mL of deionized water to form a uniform suspension. After ultrasonic treatment for 15 min, stir continuously at room temperature for 30 min, transfer the resulting suspension to a 100 ml polytetrafluoroethylene-lined reactor, and hydrothermally treat it in an oven at 160 ° C for 24 h. After cooling naturally to room temperature, the resulting precipitate is centrifuged, washed, dried, and ground to obtain a white powder. Weigh 0.1 g of the white powder and place it in a porcelain boat, which is placed in a tubular furnace under an argon atmosphere at 2 ° C·min -1 The temperature was raised to 350°C and calcined for 2 hours, and then naturally cooled and ground to obtain a ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0061] See Figure 1 The XRD spectra of ZnO prepared by the present invention and the ZnO / ZnS composite material with zinc and oxygen double vacancies show the characteristic peaks of wurtzite-type ZnO in the figure, and the peak intensity gradually decreases with the increase of sulfur content, and the position of the characteristic peak shifts to a certain extent, which shows that the ZnO / ZnS composite material formed by ion exchange can change the crystal structure of ZnO and form lattice distortion. In addition, the characteristic peaks of sphalerite-type ZnS are also shown in the figure, and the peak intensity gradually increases with the increase of sulfur content. In addition, the position of the characteristic peak belonging to ZnS shifts to a certain extent, because the insertion of S atoms makes the lattice spacing of the ZnO / ZnS composite material larger, which also shows that the ZnO / ZnS composite material with zinc and oxygen double vacancies is successfully prepared.

[0062] See Figure 2 The TEM image of the ZnO hollow sphere prepared in the present invention shows that the ZnO material has a hollow structure.

[0063] See Figure 3 From TEM of the ZnO / ZnS composite material with zinc and oxygen double vacancies (denoted as ZOS-3) prepared in the present invention, it can be seen that the composite material as a whole is still a hollow sphere structure, indicating that the morphology of the composite material prepared by ion exchange has not changed significantly.

[0064] See Figure 4 The EDS spectrum of the ZnO / ZnS composite material with zinc and oxygen double vacancies (denoted as ZOS-3) prepared in the present invention shows that ZOS-3 contains elements such as Zn, O, and S, which illustrates the successful preparation of the ZnO / ZnS composite material with zinc and oxygen double vacancies.

[0065] See Figure 5 From the EPR spectra of the ZnO hollow spheres and the ZnO / ZnS composite material with zinc and oxygen divacancies prepared in the present invention, it can be seen that ZnO only contains intrinsic O vacancy signal response, while in the ZOS composite material (denoted as ZOS-3), in addition to the enhanced O vacancy signal, a Zn vacancy signal also appears, indicating that the ZOS composite material with zinc and oxygen divacancies is successfully prepared.

[0066] The obtained ZnO / ZnS composite material with zinc and oxygen double vacancies was applied to photocatalytic water decomposition to produce hydrogen. The experimental process is as follows:

[0067] 10 mg of the photocatalyst prepared in Example 1-7 of the present invention was added to 90 mL of 0.35 mol L -1 Sodium sulfide nonahydrate and 0.25 mol L -1 The mixed solution of sodium sulfite is dispersed evenly by ultrasonication.

[0068] The suspension was transferred into a reactor and irradiated with a 300W xenon lamp as simulated sunlight. The amount of hydrogen generated was detected using an online gas chromatograph equipped with a thermal conductivity detector (TCD). The hydrogen production efficiency of the photocatalyst was further calculated based on the pre-drawn standard curve.

[0069] The efficiency of photocatalyst for decomposing water to produce hydrogen is shown in Figure 6 ,from Figure 6 It can be seen that the prepared ZnO / ZnS composite material with zinc and oxygen double vacancies and the efficiency of photocatalytic water decomposition to produce hydrogen are higher than those of ZnO, especially the ZOS-3 prepared in Example 4, whose efficiency of photocatalytic water decomposition to produce hydrogen reaches 132.51 mmol·g -1 ·h -1 , which is about 12 times that of ordinary ZnO / ZnS composites and 53 times that of ZnO hollow spheres. With the introduction of divacancies, the efficiency of photocatalytic hydrogen production of the composite material has been improved. This may be because the presence of vacancies can effectively adjust the electronic structure inside the material and greatly expand the visible light absorption range of the material. As a result, the composite material exhibits excellent photocatalytic activity and achieves efficient hydrogen evolution activity. The above results show that the introduction of divacancies is of great significance for improving the photocatalytic activity of the composite material.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a ZnO / ZnS composite material having zinc and oxygen double vacancies, characterized in that: The ZnO / ZnS composite material has a hollow spherical structure, and there are zinc vacancy and oxygen vacancy signals in the EPR spectrum of the ZnO / ZnS composite material; The preparation method of the ZnO@ZnS composite material having zinc and oxygen double vacancies comprises the following steps: A zinc salt, a template agent, and a chelating agent are mixed to prepare a precursor by a solvothermal method, and then the precursor is calcined in an air atmosphere to obtain a ZnO hollow sphere material; The ZnO hollow sphere material and thiourea are dispersed in water and mixed evenly, and then subjected to hydrothermal treatment, and then calcined in an inert atmosphere to obtain the hollow sphere.

2. The method for preparing the ZnO@ZnS composite material having zinc and oxygen double vacancies as claimed in claim 1, characterized in that: The mass ratio of zinc salt, template agent and chelating agent is 0.3-0.5:1:0.25-0.

35.

3. The method for preparing the ZnO@ZnS composite material having zinc and oxygen double vacancies as claimed in claim 1, characterized in that: The solvent for the solvothermal reaction was ethanol; Alternatively, the temperature of the solvent thermal reaction is 150-170° C., and the time is 9-11 hours.

4. The method for preparing the ZnO@ZnS composite material having zinc and oxygen double vacancies as claimed in claim 1, characterized in that The calcination temperature in air atmosphere is 450-550°C, and the calcination time is 2.5-3.5h.

5. The method for preparing the ZnO@ZnS composite material having zinc and oxygen double vacancies as claimed in claim 1, characterized in that: The temperature of the hydrothermal treatment is 155-165°C, and the time is 22-26 hours.

6. The method for preparing the ZnO@ZnS composite material having zinc and oxygen double vacancies as claimed in claim 1, characterized in that: The calcination temperature in an inert atmosphere is 300-400°C, and the calcination time is 2.5-3.5 hours.

7. Use of the ZnO@ZnS composite material having zinc and oxygen double vacancies obtained by the preparation method of claim 1 in photocatalytic water decomposition to produce hydrogen.

8. The use according to claim 7, characterized in that: The ZnO@ZnS composite material having zinc and oxygen double vacancies is added into a solution containing sodium sulfide and sodium sulfite, mixed evenly, and irradiated with light.

Citation Information

Patent Citations

  • Double-vacancy BiOCl / ZnS heterojunction catalyst as well as preparation method and application thereof

    CN115999586A